Bundling Climate Information Services (CIS) and Climate Smart Agriculture (CSA) training for extensionists and state leads of the Alluvial MC Project in Nigeria - Mvuyibwami, Patrick; Kagabo, Desire M (2022)
Agriculture remains the backbone of Nigeria’s economy, employing about 35% of the population and contributing 29.25% to real GDP in 2019. Despite its importance, the sector faces critical challenges, including limited access to land, low irrigation development, poor infrastructure, and increasing climate risks such as variability in rainfall, rising temperatures, and pest infestations. To address these vulnerabilities, the Alliance of Bioversity International and CIAT, in collaboration with the Alluvial MC project, organized three Climate Information Services (CIS) trainings in June 2022 across Abuja, Kano, and Yola. The trainings, structured as Training of Trainers (ToTs), targeted project extensionists and state leads from Nigeria’s three agricultural regions. They focused on strengthening capacity to access, understand, and use CIS for improved crop production, particularly in rice, maize, and soybean value chains. The sessions emphasized the use of tools such as the Digital AgroClimate Advisory (DACA) app and Participatory Integrated Climate Services for Agriculture (PICSA), enabling participants to link seasonal forecasts with farmer needs and disseminate actionable climate-smart practices.